Acid pretreatment of wc-co for surface roughening and cobalt removal prior to CVD diamond coating - Norafifah, H. (2013)
Chemical vapor deposition (CVD) diamond coatings a re being developed to be applied on carbide cutting tools to enhance wear resistance an d increase tool life. As a prerequisite, for ensuri ng adhesion of CVD diamond on tungsten carbide substra te, it is necessary to prepare high surface roughness and to remove the cobalt on tungsten carb ide surface during the pretreatment. In this study, a two step acid pretreatment was examined for those purposes. Etching using modified Murakami’s reagent was initially performed to roughen the surf ace. Subsequently, the carbide was immersed in nitric acid to remove cobalt. Concentration of the acid solutions and reaction time were varied. Results showed that the initial step by modified Mu rakami’s reagent etching resulted in a surface roughness of Ry = 6.95 μm, which is a 15% increase from the averag e initial surface roughness. The second step by nitric acid immersion on modified Mu rakami’s reagent etched carbide samples resulted in carbide surfaces with zero cobalt conte nt, confirming the effectiveness of the pretreatmen t.